War and Peace in Modern Hindu Thought—Gandhi, Aurobindo, and Vivekananda in Conversation - Jeffery D. Long (Religions)
Mohandas Gandhi (1869–1948) and Aurobindo Ghose (1872–1950) hold distinct, yet overlapping, positions on the topic of war and peace, violence and nonviolence, and how evil ought to best be confronted. To some extent, the overlaps in their views can be seen as an effect of them basing their respective ideals on a shared foundation of Hindu teaching. More specifically, at least some portion of this overlap can potentially be seen as a function of the influence exerted upon both of these thinkers by the teachings of Swami Vivekananda, who was an inspiration to many modern Hindu thinkers, including both Gandhi and Ghose, as both figures attest. This paper will argue, apart from any historical influence he may or may not have had upon them, that Gandhi’s and Ghose’s views both, in different senses, comport well with the teaching of Swami Vivekananda. Specifically, the argument will be what could be called the utopian and realist orientations of Gandhi and Ghose, respectively, regarding the topic of violence, and we can find a logical reconciliation in Vivekananda’s philosophy of karma yoga: the path to liberation through service to the suffering beings of the world.